Cervical Disc Arthroplasty: Current Evidence and Real-World Application. Issue 6 (6th January 2018) - Nunley, Pierce D; Coric, Domagoj; Frank, Kelly A; Stone, Marcus B
Abstract: Cervical total disc replacement (cTDR) is still considered a developing technology, with widespread clinical use beginning in the early 2000s. Despite being relatively new to the marketplace, the literature surrounding cTDR is abundant. We conducted a thorough review of literature published in the United States (US) and outside the US to report the current global state of cTDR research and clinical use. Search criteria were restricted to publications with a clinical patient population, excluding finite element analyses, biomechanical studies, cadaver studies, surgical technique-specific papers, and case studies. US publications mostly encompass the results of the highly controlled Food and Drug Administration Investigational Device Exemption trials. The predominantly level I evidence in the US literature supports the use of cTDR at 1 and 2 surgical levels when compared to anterior cervical discectomy and fusion. In general, the outside the US studies typically have smaller patient populations, are rarely controlled, and include broader surgical indications. Though these studies are of lower levels of evidence, they serve to advance patient indications in the use of cTDR. Complications such as secondary surgery, heterotopic ossification, and adjacent segment degeneration also remain a focus of studies. Other external challenges facing cTDR technology include regulatory restrictions and health economics, both of which are beginning to be addressed. Combined, the evidence for cTDR is robust supporting a variety of clinical indications.